Integrating Network Pharmacology and Metabolomics to Elucidate the Mechanism of Action of Huang Qin Decoction for Treament of Diabetic Liver Injury - Xu, Xiaomin; Fang, Cheng; Wang, Yu; Lu, Fang; Liu, Shumin (Frontiers in Pharmacology, 2022)
Abstract Aim of the study To investigate the mechanism of Huang Qin Decoction (HQD) on diabetic liver injury (DLI) using network pharmacology and metabolomics. Materials and methods The protective effect of HQD on DLI and its mechanism were investigated utilizing metabolomics and network pharmacology analysis. Explore the important pathways of biomarkers identified in metabolomics analysis, then conduct network pharmacological analysis to identify the likely target of HQD, and finally perform molecular docking to explore the interaction between biomarkers and target proteins. Results A metabolomics investigation revealed that HQD included 18 possible compounds implicated in the therapy of DLI. The majority of these metabolites are regulated to recover following HQD treatment. We identified 10 key genes using network pharmacology, which is partially compatible with the results of metabolomics. The additional detailed investigation focused on three major targets, including PTGS2, MAPK3, and AKT1, and their essential metabolites and pathway. The significant affinity of the primary target for the HQD was confirmed by molecular docking. Conclusion This research examined the main targets and mechanisms of HQD in treating DLI using metabolomics and network pharmacology analysis. It is beneficial to develop HQD as a supplement medicine for the treatment DLI.